Expression of toll-like receptor (TLR) 2 on macrophage infected with rBCG clone expressing MSP-1C of Plasmodium falciparum and its effect on IL-12 and IL-lp production - Ali, Nursyazana Aqilah (Universiti Sains Malaysia, 2015)
Toll like receptor (TLR) is a pattern recognition receptor (PRRs) that involve in innate immune response against invading pathogen during phagocytosis. TLR controls the transcription of inflammatory response by the infected cells. Among the TLRs identified, TLR2 is one of the receptor that involved in the recognition of mycobacterium and malaria parasites by macrophages. This study was conducted to determine the expression of the TLR2 protein in a mouse macrophage cell line infected with BCG and recombinant BCG (rBCG) expressing the C-terminus of merozoite surface protein (MSP-1C) of Plasmodium falciparum by Western blot. The role of the TLR in the production of pro-inflammatory cytokine production such as IL-12 and IL-ip was also evaluated in the supernatant of infected cells in the presence or absence of TLR2 inhibitor and LPS+IFN-y stimulation using ELISA. The result demonstrated that both BCG- and rBCG-infected macrophages express significant TLR2 protein. However, the expression of TLR2 by the rBCG-infected macrophages was significantly higher than those expressed by BCG-infected macrophages. For the cytokine production, the presence of TLR2 inhibitor does not affect the production of IL-12, but capable to reduce the production of IL-ip by the macrophage infected with both BCG and rBCG. In conclusion, our results indicate that the macrophage expresses TLR2 receptor during BCG and rBCG infection. However, this TLR2 receptor only important for the production of IL-ip cytokine but not the production of IL-12 cytokine by the macrophages.